2016
DOI: 10.1371/journal.ppat.1005404
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi BBK32 Inhibits the Classical Pathway by Blocking Activation of the C1 Complement Complex

Abstract: Pathogens that traffic in blood, lymphatics, or interstitial fluids must adopt strategies to evade innate immune defenses, notably the complement system. Through recruitment of host regulators of complement to their surface, many pathogens are able to escape complement-mediated attack. The Lyme disease spirochete, Borrelia burgdorferi, produces a number of surface proteins that bind to factor H related molecules, which function as the dominant negative regulator of the alternative pathway of complement. Relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
222
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(240 citation statements)
references
References 96 publications
17
222
0
1
Order By: Relevance
“…Recently, it was shown that the fibronectin and glycosaminoglycan binding protein, BBK32, is able to bind to the complement component C1 cleavage product, C1r, and inhibit its activation (Garcia, Zhi, Wager, Höök, & Skare, ). This binding activity on the surface of B. burgdorferi was found to inhibit in vitro complement activation through the classical pathway, in vitro (Garcia et al, ). Interestingly, two studies of mice deficient in complement component C3 suggested that complement‐mediated defence diminishes the bacterial burden in a variety of tissues, particularly at 2 weeks after infection (Lawrenz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the fibronectin and glycosaminoglycan binding protein, BBK32, is able to bind to the complement component C1 cleavage product, C1r, and inhibit its activation (Garcia, Zhi, Wager, Höök, & Skare, ). This binding activity on the surface of B. burgdorferi was found to inhibit in vitro complement activation through the classical pathway, in vitro (Garcia et al, ). Interestingly, two studies of mice deficient in complement component C3 suggested that complement‐mediated defence diminishes the bacterial burden in a variety of tissues, particularly at 2 weeks after infection (Lawrenz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways by which bacterial pathogens block the complement system; these include capsule production [49,50], modification of LPS DOI: 10.1159/000491439 [51,52], recruitment of human complement regulators to the bacterial surface (C4BP, factor H, and FHL-1) and production of proteases that cleave complement components [46]. Furthermore, bacteria produce specific complement inhibitory molecules that block specific steps in the complement cascade; for example, bacteria can frustrate the activation of C1s [53,54], block C3 and C5 convertases [20,55], block C5 cleavage [56,57], prevent C5aR activation [58], or inhibit MAC formation [59]. For more detailed information on these evasion mechanisms, we refer to an extensive review on this topic [46].…”
Section: Complement Evasion Strategies By Pathogenic Organismsmentioning
confidence: 99%
“…The multi-stage process of complement activation presents spirochetes (such as B. burgdorferi ) with the opportunity to attack at multiple phases. For example, B. burgdorferi binds and inhibits the C1 initiation complex and accelerates C3b inactivation (91, 125). Furthermore, B. burgdorferi can bind either Factor H or FHL-1, two important complement regulators which upon being bound by CRASP-2 and CRASP-1 ( B. burgdorferi membrane-bound lipoproteins), respectively, are inactivated and inhibit formation of complement system activation products (126, 127).…”
Section: Modulatory Effects Of Spirochetal Lipoproteins Related To Famentioning
confidence: 99%